The Influence of Training Methods and Motivation on Junior High School Students' 100 Meters Running Abilities - Dwi Nata, Anggri; Dirneti, Dirneti; Yeni , Hilda Oktri; Kurniawan, Edi; Indrawan, Indrawan; Igoresky, Andre (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research aims to determine the effect of the intensive interval method, repetition method and motivation on 100 meter sprint performance. This type of research is a quasi-experiment (with a 2x2 factorial design. The population of this research is students of SMP N 2 Pangkalan Limapuluh Kota, totaling 195 people, while the sample of this research is 48 people who are divided into two groups, 27% students with high motivation and 27% with low motivation. motivation. The instruments used in this research were motivation tests and speed tests in the 100 meter sprint performance. Data were analyzed using a two-way analysis of variance technique (ANAVA 2x2). The results of data analysis show that: (1) there is a difference in the achievement of 100 meter sprint speed between the group that used the intensive interval series method and the group that used the repetition series method, (2) there was an interaction between the training method and the level of motivation in increasing the speed of sprint performance. 100 meters, (3) at a high level of motivation, the intensive interval series method is more effective than the repetition series method in improving the 100 meter sprint performance of junior high school students, (4) Furthermore, at low motivation, the repetition series method is more effective than the intensive interval method in Junior high school students' 100 meter short distance running performance